STRATEGIC TRANSFORMATION AND COMPETITIVENESS OF COMMERCIAL BANKS IN UZBEKISTAN: A CONCEPTUAL AND METHODOLOGICAL APPROACH (World Economics and Finance Bulletin, 2026)
This article examines the processes of strategic transformation of commercial banks and their impact on the formation of competitiveness in the context of developing financial markets. Using the example of the Republic of Uzbekistan, key structural changes in the banking sector are identified, and an integrated conceptual model of competitiveness is developed, taking into account the interaction of financial, technological, and institutional factors. The findings have both theoretical and practical significance for improving banking policy and the development strategies of financial institutions.
Keywords: Competitiveness; commercial banks; strategy; transformation